Depression Following Major Life Transitions in Women: A Review and Theory. Issue 5 (October 2020) - Moustafa, Ahmed A.; Crouse, Jacob J.; Herzallah, Mohammad M.; Salama, Mohamed; Mohamed, Wael; Misiak, Błażej; Frydecka, Dorota; Al-Dosari, Nasser F.; Megreya, Ahmed M.; Mattock, Karen
Depression can occur due to common major life transitions, such as giving birth, menopause, retirement, empty-nest transition, and midlife crisis. Although some of these transitions are perceived as positive (e.g., giving birth), they may still lead to depression. We conducted a systematic literature review of the factors underlying the occurrence of depression following major life transition in some individuals. This review shows that major common life transitions can cause depression if they are sudden, major, and lead to loss (or change) of life roles (e.g., no longer doing motherly or fatherly chores after children leave family home). Accordingly, we provide a theoretical framework that explains depression caused by transitions in women. One of the most potential therapeutic methods of ameliorating depression associated with life transitions is either helping individuals accept their new roles (e.g., accepting new role as a mother to ameliorate postpartum depression symptoms) or providing them with novel life roles (e.g., volunteering after retirement or children leave family home) may help them overcome their illness.